Implementasi Permainan Ranking 1 Sebagai Model Pembelajaran IPS Kelas 5 Di Sekolah Dasar - Ananda, Dena Windi; Susilawati, Susilawati; Ridwan, Ita Rustiati (Didaktika, 2023)
Learning cannot be separated from teacher teaching methods and models. This research was motivated by the use of learning models in social studies classes that are still not effective, therefore making the classroom environment less conducive. Learning activities, especially social studies, must be fun to contain historical value for students. For elementary school students, form a playful lesson model so that it is easy to understand and apply to life. The coveted model to achieve the goal of learning social studies is the Rank 1 game model. The objectives to be achieved in this study must be identified, analyzed and explained 1) how the implementation of the Ranking 1 game as a fifth-grade social studies learning model at the State Elementary School of Sajira 01, 2) improve student learning outcomes through the Ranking 1 Game as a fifth-grade social studies learning model in Elementary School. This research is qualitative research with classroom action research (CAR). The procedure in this study uses the theory developed by Kemmis and McTaggart. This study showed significant changes in student learning outcomes, indicated by increased student engagement with learning activities and increased academic performance, as evidenced by test scores. The average value obtained in the first cycle of learning outcomes was 83.7 and increased to 96.3 in the second cycle. Therefore, the researcher recommends the application of the Ranking 1 game model as an alternative that provides a more meaningful learning experience, especially when learning social studies subjects.